Proposta de método de avaliação da sustentabilidade para a remediação de áreas contaminadas - Braun, Adeli Beatriz (2018)
The remediation of contaminated areas is not automatically sustainable. Thus, sustainable remediation emerges with a broad and holistic approach, also considering the three dimensions of sustainability in the decision making on the remediation of contaminated areas. Evaluate both impacts and benefits on environmental, economic and social aspects throughout all the process. However, the key factors for the analysis and application of sustainability in this context, especially with regard to decision support methods, do not yet have a universally consolidated and standardized approach. In this sense, this study aimed to define a method of evaluation of sustainability applied to the remediation of contaminated areas that best represents the discourse of sustainable remediation. The methodology consisted of six main steps, starting with the identification and description of the sustainable remediation methods being developed in the world scenario, followed by the diagnosis and selection of important criteria to evaluate the methods for the effective approach to sustainable remediation. The third step consisted of analyzing the methods for the structure and approach, as well as their comparison with the selected criteria, in order to verify the level of satisfaction of these by the methods. In the sequence, the selected criteria were submitted to the judgment of stakeholders of the area, through the multicriteria analysis process, the Analytic Hierarchy Process (AHP). In the fifth step, the information was compiled, and the weighting levels obtained in the previous step were used to calculate the degree of sustainability of each identified method, which guided the selection of the best method under the conditions considered. And finally, an optimization of the selected method was suggested in order to obtain the ideal method and that better represents the premises of the sustainable remediation. The results indicated a tendency among the eight methods identified in providing, in their structure, a graphical representation for the decision making. The multicriteria analysis pointed out, among the nine criteria selected and analyzed, the "Protection of human health and the environment in general" being the most important criterion among the judgments of the participating decision makers. In this analysis, the method from ITRC (Interstate Technology and Regulatory Council) obtained a better performance, reaching a sustainability level of 87.5%, considering the levels of satisfaction of all the criteria, as well as the weighting factors obtained for them. Thus, the ITRC method was optimized to a 100% approach to the criteria considered, which defined it as the ideal method and that best represents the discourse of sustainable remediation. Therefore, the degree of sustainability obtained was to verify the relevant and deficient aspects of the methods, as well as to identify the areas that need improvement, both for existing methods, but mainly to guide the development of new methods applied to sustainable remediation. Also, it was concluded that the analysis of the methods, in relation to criteria judged and weighted in the context of sustainable remediation, provides a more detailed understanding of the contributions of the most different methods to sustainable results.